Corruption culture and corporate misconduct - Liu, Xiaoding (Journal of Financial Economics, 2016)
Despite significant interest in corporate culture, there is little empirical research on its role in influencing corporate misconduct. Using cultural background information on key company insiders, I construct a measure of corporate corruption culture, capturing a firm's general attitude toward opportunistic behavior. Firms with high corruption culture are more likely to engage in earnings management, accounting fraud, option backdating, and opportunistic insider trading. I further explore the inner workings of corruption culture and find evidence that it operates both as a selection mechanism and by having a direct influence on individual behavior.